Lower-dose corticosteroid therapy in severe immune thrombocytopenia during pregnancy: The comparable efficacy and lower incidence of maternal complications - Xu, Xue; Liang, Mei-Ying; Wang, Yi-Lin; Wang, Jian-Liu; Zhang, Xiao-Hui (Frontiers in Pharmacology, 2022)
Background: This study assessed the clinical efficacy of oral prednisone at low dose (LD) versus the previous high-dose (HD) study in patients with severe immune thrombocytopenia during pregnancy and its side effects on maternal and neonatal outcomes. Study design: Pregnant patients with ITP were enrolled in the study (platelet count <30×109/L) between January 2015 and 2019. A total of 43 patients received LD oral prednisone (0.25–0.5 mg/kg) as the initial treatment and were compared retrospectively with the 31 patients in the HD (1 mg/kg) study. The primary clinical endpoint was the response rate, and the secondary endpoint was maternal hemorrhagic events, complications, and neonatal outcomes. Results: In total, 35% of patients responded (15/43) to the LD cortico-therapy, including four patients with a complete response which was no less than HD therapy (35.5%). The bleeding symptoms of 10 (30%) patients were ameliorated after 14 days of LD prednisone treatment. Preeclampsia occurred in three cases (7% of total) of which the incidence was obviously lower than that of the previous study at HD (18%). No stillbirth or miscarriage occurred in the LD group, and neonatal outcomes had no significant differences between the two studies. Conclusion: LD prednisone therapy for severe ITP patients during pregnancy had equal efficacy to HD treatment. In addition, the decrease in dosage significantly reduced the incidence of hypertension.